Islanding detection with universal grid-forming inverter-based generation - Laaksonen, Hannu (Institution of engineering and technology, 2023)
One major concern of commonly proposed grid-forming (GFM) inverter-based resources (IBRs) has been the unintentional islanding, because the variables that are typically used for islanding detection of GFMs are different than those traditionally used with grid-following (GFL) IBRs. Therefore, this paper studies the effect of recently proposed new universal frequency-locked-loop (U-FLL) -based GFM synchronization method on islanding detection with different passive methods like voltage vector shift, positive sequence voltage angle difference, voltage unbalance and voltage total harmonic distortion. The PSCAD simulations are done with 100 % IBR-based system as well as with hybrid power system including IBR-based distributed energy resources (DER) and synchronous generation (SG). Based on the simulations it can be concluded that the recently proposed universal U-FLL GFM method does not risk the operation of the traditional passive islanding detection schemes unlike some other commonly proposed GFM control methods.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|